From Anti-Vax Intentions to Vaccination: Panel and Experimental Evidence from Nine Countries - Vincenzo Galasso; Vincent Pons; Paola Profeta; Michael Becher; Sylvain Brouard; Martial Foucault (Center for Economic Studies and ifo Institute (CESifo), 2022)
Millions of people refuse COVID-19 vaccination. Using original data from two surveys in nine OECD countries, we analyze the determinants of anti-vax intentions in December 2020 and show that half of the anti-vax individuals were vaccinated by summer 2021. Vaccinations were more likely among individuals aged 50+, exposed to COVID-19, compliant with public restrictions, more informed on traditional media, trusting scientists, and less concerned about vaccines' side effects. We run a survey experiment with informational messages. In EU countries, a message about protecting health largely increases vaccinations, even among anti-vax individuals. In the U.K. and U.S., a message about protecting the economy generates similar effects. Our findings suggest that informational campaigns should adopt adequate narratives and address concerns about vaccines' side effects.
Keywords: I12; D83; 330; Covid-19 vaccination; randomized experiment; information transmission